2014
DOI: 10.1002/2014jc010351
|View full text |Cite
|
Sign up to set email alerts
|

The effect of water temperature on air entrainment, bubble plumes, and surface foam in a laboratory breaking-wave analog

Abstract: Air-entraining breaking waves form oceanic whitecaps and play a key role in climate regulation through air-sea bubble-mediated gas transfer, and sea spray aerosol production. The effect of varying sea surface temperature on air entrainment, subsurface bubble plume dynamics, and surface foam evolution intrinsic to oceanic whitecaps has not been well studied. By using a breaking wave analog in the laboratory over a range of water temperatures (T w 5 5 C to T w 5 30 C) and different source waters, we have examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 58 publications
3
57
2
Order By: Relevance
“…Controlled experiments with genuine seawater are rare (e.g. Chanson et al 2006, Blenkinsopp and Chaplin 2011, Callaghan et al 2014. In strongly aerated regions (void fractions > 2%), the results showed differences between freshwater, saltwater (synthetic seawater) and genuine seawater in terms of void fraction and bubble sizes.…”
Section: Water Solution: Freshwater Saltwater or Seawater?mentioning
confidence: 98%
“…Controlled experiments with genuine seawater are rare (e.g. Chanson et al 2006, Blenkinsopp and Chaplin 2011, Callaghan et al 2014. In strongly aerated regions (void fractions > 2%), the results showed differences between freshwater, saltwater (synthetic seawater) and genuine seawater in terms of void fraction and bubble sizes.…”
Section: Water Solution: Freshwater Saltwater or Seawater?mentioning
confidence: 98%
“…2,5,6,14 Detailed studies of SSA production methods have shown that both breaking waves and plunging waterfall techniques replicate ambient SSA subpopulations of particles with the proper size and physical and chemical properties. 2,5 Other variables, such as temperature, 15 surfactant chemistry, 13,16 and white cap foam formation 5 are also critical factors in producing real world SSA populations. The development of these innovative laboratory-based methods has opened the doors for exploring the composition, reactivity, and properties of a globally abundant tropospheric aerosol, fresh SSA, under controlled conditions.…”
Section: ■ Producing Representative Ssamentioning
confidence: 99%
“…The system is ideal for laboratory experiments where high-frequency sampling is beneficial, for example in studies of gas exchange and gas partitioning during ice formation and melt (Loose et al, 2009a;Lovely et al, 2015), and studies of air-water gas exchange using wind-wave tanks or bubble plume generators (Asher et al, 1996;Callaghan et al, 2014;Krall and Jähne, 2014;Mesarchaki et al, 2015b;Nagel et al, 2015). It could be used for continuous, high-frequency monitoring of surface waters in order to improve understanding of physically-driven gas fluxes, and be used alongside instruments measuring the fluxes of biologically-active gases (Cassar et al, 2009;Rafelski et al, 2015).…”
Section: Future Directionsmentioning
confidence: 99%